2002
DOI: 10.1108/10222529200200012
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the internal auditing function: Processes and procedures

Abstract: Internal auditing assumes an increased responsibility for the evaluation of entity operations as a service to management and the board of directors. Quality assurance review is the process through which assurance is obtained that the internal auditing department’s work is done in accordance with the Standards for the Professional Practice of Internal Auditing. This study examines the current practices of quality assurance review in South Africa. Although not all organisations surveyed do perform internal audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…İç tetkikler: Kalite yönetiminin uygunluğunu ve performansını ölçmek için sistemin şartlarının etkili olarak uygulandığını ve sürekliliğinin takip edildiği objektif kayıtlarla ispatlandığına dair belirlenen şartların yerine getirildiğinin tetkikçiler tarafından kontrolüdür. Yönetimin gözden geçirmesi: Kalite yönetiminin amacına uygunluğu, yeterliliği, etkinliği ve kuruluşun stratejik tarafı ile uyumlu olmasını güvence altına alarak, kuruluşun üst yönetiminin planlı aralıklarla kalite yönetim sistemi toplantıları yapması ve yapılan bu toplantılarda belirlenen konuları gözden geçirmesidir (TS EN ISO 19011 Kalite ve Çevre Yönetim Sistemleri Tetkik Kılavuzu). Kalite yönetim sisteminde tetkikler; iç tetkik, tedarikçi tetkiki ve belgelendirme tetkikleri olmak üzere üç grupta gerçekleşmektedir.…”
Section: Kalite Yönetim Sistemi Performansı öLçümünde Kullanılan Tetk...unclassified
“…İç tetkikler: Kalite yönetiminin uygunluğunu ve performansını ölçmek için sistemin şartlarının etkili olarak uygulandığını ve sürekliliğinin takip edildiği objektif kayıtlarla ispatlandığına dair belirlenen şartların yerine getirildiğinin tetkikçiler tarafından kontrolüdür. Yönetimin gözden geçirmesi: Kalite yönetiminin amacına uygunluğu, yeterliliği, etkinliği ve kuruluşun stratejik tarafı ile uyumlu olmasını güvence altına alarak, kuruluşun üst yönetiminin planlı aralıklarla kalite yönetim sistemi toplantıları yapması ve yapılan bu toplantılarda belirlenen konuları gözden geçirmesidir (TS EN ISO 19011 Kalite ve Çevre Yönetim Sistemleri Tetkik Kılavuzu). Kalite yönetim sisteminde tetkikler; iç tetkik, tedarikçi tetkiki ve belgelendirme tetkikleri olmak üzere üç grupta gerçekleşmektedir.…”
Section: Kalite Yönetim Sistemi Performansı öLçümünde Kullanılan Tetk...unclassified
“…Theoretically, efficiency and effectiveness of auditing establishes greater clients' trust on the products/services of the organization and their operations (Fuentes et al, 2000). In a study conducted by Venter and Du Bruyn (2002), the authors showed that audit efficiency and effectiveness requires a strong framework to function as a benchmark standard in order to assess the system and demonstrate its suitable structure, effectiveness and overall functioning.…”
Section: Literature On Efficiency and Effectiveness Of Auditingmentioning
confidence: 99%
“…[13]  Preliminary analytical procedure is exercised through unrealistic (unaudited) financial reports [14] might obscure true financial representation of auditee [15].  Substantive test of internal control involves procedures examination using normal sample provided by auditee [16] might cover bigger transaction infringing related procedures [17]. Audit Sampling (SAS No.1) There are two approaches: 1.…”
Section: Obsolescence Of Current Financial Auditmentioning
confidence: 99%